2015
DOI: 10.1021/jf5026373
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Intestinal Microbiota Is Associated with Lower Plasma Cholesterol and Weight Gain in Hamsters Fed Chardonnay Grape Seed Flour

Abstract: The relationship between the intestinal microbiota and the hypocholesterolemic and antiobesity effects of whole grape seed flour from white and red winemaking was evaluated. Male Golden Syrian hamsters were fed a high-fat (HF) control diet or a HF diet supplemented with 10% partially defatted grape seed flours from either Chardonnay (ChrSd) or Cabernet Sauvignon (CabSd) grapes for 3 weeks. The numbers of total bacteria and relative abundances of Bifidobacterium spp., Lactobacillus spp., and Firmicutes in feces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 65 publications
4
35
1
1
Order By: Relevance
“…Although the biological significance of hepatic Tlr5 downregulation is unclear, ChrSd supplementation may reduce the gut bacterial residence-derived inflammatory response to HF-induced stress. In our previous study, the composition of gut microbiota was altered by ChrSd supplementation, which was related to expression of intestinal fibroblast growth factor ( Fgf15 ) and hepatic genes regulating cholesterol and lipid metabolism [58]. Collectively, these findings indicate that ChrSd supplementation prevents HF diet-induced inflammation of the liver by downregulating hepatic expression of genes related to immune and inflammatory pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Although the biological significance of hepatic Tlr5 downregulation is unclear, ChrSd supplementation may reduce the gut bacterial residence-derived inflammatory response to HF-induced stress. In our previous study, the composition of gut microbiota was altered by ChrSd supplementation, which was related to expression of intestinal fibroblast growth factor ( Fgf15 ) and hepatic genes regulating cholesterol and lipid metabolism [58]. Collectively, these findings indicate that ChrSd supplementation prevents HF diet-induced inflammation of the liver by downregulating hepatic expression of genes related to immune and inflammatory pathways.…”
Section: Discussionmentioning
confidence: 91%
“…The intensity of green and red reflect the correlation strength, based upon the amount of times it was reported. Correlations were observed in caecal microbiota of DIO mice receiving prebiotics , caecal microbiota of DIO or control mice, supplemented with or without prebiotics , faecal microbiota of metformin‐treated DIO mice , faecal microbiota of DIO rats receiving probiotics , faecal microbiota of DIO rats , caecal microbiota of DIO mice receiving prebiotics , faecal microbiota of elderly receiving probiotics , small intestinal microbiota of DIO mice receiving prebiotics and probiotics , faecal microbiota of pregnant obese women receiving inulin treatment , faecal microbiota of humans of different weight , faecal microbiota of healthy humans on a high‐fat high‐sugar diet for 4 weeks , caecal microbiota of DIO mice undergoing bariatric surgery , faecal microbiota of overweight and obese humans , faecal microbiota of DIO hamsters receiving prebiotic treatment , faecal microbiota of mice receiving different fat diets , faecal microbiota of DIO rats , caecal microbiota of DIO mice . The bacteria are from the phylum (P), order (O), family (F), genus (G) or species (S) level.…”
Section: Intestinal Microbiota Composition Associated With Diet‐inducmentioning
confidence: 99%
“…To identify potentially beneficial and detrimental bacteria for obesity development, we review the HFD‐induced effects on common parameters related to obesity and on the rodent microbiota . A number of significant correlations between the human or rodent microbiota and several common parameters related to obesity have been reported (Table ) . Additionally, a number of consistent associations have been reported (Table S1), including studies in which a specific bacterial taxonomic group is more abundant in situations where body weight is increased after HFD feeding in rodent models.…”
Section: Intestinal Microbiota Composition Associated With Diet‐inducmentioning
confidence: 99%
“…This hypothesis is supported by findings from a murine model of high-fat diet–induced nonalcoholic fatty liver disease, for which antibiotic treatment altered bile acid composition and inhibited FXR signaling in the ileum, but not in the liver 27 . Similarly, altering microbial composition via probiotic administration 28 or administration of a high-fat diet29, 30 is associated with reduced activity of the FXR/FGF15 signaling axis. Further studies are required to confirm if the disturbed intestinal FXR response observed in SBS piglets in response to OCA is owing to microbial dysbiosis and consequent bile acid dysmetabolism or owing to alternative activation of CYP3A4, which may impact on bile acid metabolism.…”
Section: Discussionmentioning
confidence: 75%